Identification of Fungi Decomposers on Acacia mangium Leaf Litter - Lestari, Iing Dwi (Proceeding International Conference on Global Resource Conservation, 2013)
In nature, decomposer fungi have an important role on the decomposisition organic matters to inorganic compound. This research aimed to identify fungi decomposersfound inleaf litter of Acacia mangium. A. mangium is one of the plant spesies is used for revegetationin mined landswhich produce litter. Fungiwere isolated from leaf litter of A.mangium and grown in PDA medium. Indentifications of fungi are based on the structure and characters of fungal colonies. 7 species of fungi was found, those are Fusarium sp3, two spesies of Basidiomycetes, sterile myselia, Tichoderma sp1., Paecilomyces sp3., and Penicillium sp1. This finding suggest the process of fungal succession on leaf litter in mining land.Keywords: A. mangium, Decomposer fungi, leaf litter, mined land.Â